An Analysis of the Four Language Skills Tests Based on Language Assessment and Evaluation Principle at SMP Negeri 1 Pematangsiantar - sembiring, Yena Jorena; Devi Triana; Sinaga, Mutiara Angelica; Silaban, Monika Natalina; Silalahi, Dumaris E. (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
This research analyze the implementation of English language assessments for listening, speaking, reading, and writing based on the principles of validity, reliability, practicality, authenticity, and washback.The assessment is administered into 27 students of seventh grade at SMP Negeri 1 Pematangsiantar. The research aims to evaluate how the designed assessments align with effective assessment principles while addressing classroom realities.The quality of the test is analyzed by using mixed-method approach, quantitative analysis utilized the Pearson Product-Moment and Split-Half methods to measure validity and reliability, while qualitative analysis examined practicality, authenticity, and washback through observation and student feedback. The findings indicate that while several test items fulfilled validity and reliability criteria, many required revision to enhance alignment with learning objectives and improve consistency. Practicality was evident as the assessments could be conducted within time and resource limitations, although challenges appeared in scoring and analysis processes. Authenticity was reflected in the use of materials and tasks closely related to students' daily contexts, promoting meaningful language use. Additionally, the assessments generated positive washback, motivating students to engage actively in learning while providing teachers with insights for instructional improvement. These results highlight the significance of designing assessments that are not only aligned with curriculum goals but also promote comprehensive language skill development. The research contributes to enriching assessment literacy among pre-service teachers and emphasizes the continuous need for reflection and refinement in language assessment practices to foster effective English learning environments in EFL contexts.